Evaluation of liposome toll‐like receptor ligand complexes for non‐specific mucosal immunoprotection from feline herpesvirus‐1 infection. (7th March 2019) - Contreras, Elena T.; Olea‐Popelka, Francisco; Wheat, William; Dow, Steven; Hawley, Jennifer; Lappin, Michael R.
Abstract : Background: Feline herpesvirus‐1 (FHV‐1) infection can result in serious morbidity and mortality, especially in kittens. Immunotherapy using liposome‐toll‐like receptor (TLR) ligand complexes (LTC) has been shown to activate innate immune responses. Objectives: To determine in kittens whether mucosal administration of LTC before FHV‐1 inoculation would decrease severity of clinical signs and decrease quantities of FHV‐1 DNA in materials collected on oropharyngeal swabs. Animals: Nineteen, 14‐week‐old, purpose‐bred kittens. Methods: Pilot clinical trial with 2 groups of kittens allocated to either an LTC or control group. The LTC were administered into both nares and the oropharynx of the 12 LTC group kittens, and all 19 kittens were inoculated with FHV‐1 24 hours later. Clinical scores were determined daily for 28 days, and oropharyngeal mucosal materials were collected every 7 days to assess FHV‐1 DNA quantities for comparison between groups. Results: Conjunctivitis was more common in kittens in the control group on Days 15‐28 ( P = .01) and Days 1‐28 ( P = .02). Total respiratory scores were higher in the LTC group on days 15‐28 ( P = .03). The LTC group had significantly decreased FHV‐1 DNA on swabs when compared to the control group on some postinoculation days, using 2 methods of calculation. Conclusions and Clinical Importance: Administration of LTC to kittens was shown to decrease FHV‐1 DNA and some manifestations of illness in kittens when administrated 24 hours before inoculation, suggesting clinical benefit.